2017
DOI: 10.1021/acsomega.7b00264
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of Structure II Methyl Vinyl Ketone Binary Clathrate Hydrates and Effects of Secondary Guest Molecules on Large Guest Conformation

Abstract: Clathrate hydrates have received massive attention because of their potential application as energy storage materials. Host water frameworks of clathrate hydrates provide empty cavities that can capture not only small molecular guests but also radical species induced by γ-irradiation. In this work, we investigated structure II methyl vinyl ketone (MVK) binary clathrate hydrates with CH 4 , O 2 , and N 2 and the effects of secondary guest spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Gauche I was the most stable conformation, and both Anti conformers (6.78 kJ/mol for Anti I and 6.83 kJ/mol for Anti II) were less stable than the three Gauche conformers (0 kJ/mol for Gauche I, 4.62 kJ/mol for Gauche II, and 3.91 kJ/mol for Gauche III). Although the Gauche conformers of CPM may be preferred in terms of potential energy, many recent reports indicate that hydrocarbon guest molecules are sometimes enclathrated as a relatively less stable conformation. Because the energy differences among the five conformers were small, they were all considered potential candidates for enclathration in the hydrate cage if the formation of the binary CPM + CH 4 clathrate proved possible.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gauche I was the most stable conformation, and both Anti conformers (6.78 kJ/mol for Anti I and 6.83 kJ/mol for Anti II) were less stable than the three Gauche conformers (0 kJ/mol for Gauche I, 4.62 kJ/mol for Gauche II, and 3.91 kJ/mol for Gauche III). Although the Gauche conformers of CPM may be preferred in terms of potential energy, many recent reports indicate that hydrocarbon guest molecules are sometimes enclathrated as a relatively less stable conformation. Because the energy differences among the five conformers were small, they were all considered potential candidates for enclathration in the hydrate cage if the formation of the binary CPM + CH 4 clathrate proved possible.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to assign the conformation of CPM in the large cages of sII hydrate as a dynamic Anti form (Anti I or Anti II). 45,46,50,51 Figure 3 shows the Raman spectra of the binary CPM + CH 4 hydrate, which were used to investigate the guest inclusion behavior. As indicated by the 13 C NMR spectra, a weak Raman signal at 2902 cm −1 corresponded to the inclusion of CH 4 molecules in the sII-L cages, and a strong signal at 2913 cm −1 showed that CH 4 was present in the sII-S cages (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous organic compounds can act as hydrate formers and are not limited to hydrocarbons. Diverse sII and sH formers contain various functional groups have been reported thus far, including hydroxyl, ether, ketone, ,, amine, nitro, , and others. The ability of a compound to act as a hydrate former and the specific hydrate structure it forms primarily depends on its size, although other factors also influence it. For example, diisopropyl amine is an sH former, whereas 2,4-dimethylpentane and diisopropyl ether are not, despite being isoelectric and exhibiting similar structures and size.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiating solid crystalline materials with high-energy protons or electrons has emerged as a novel approach to lattice engineering because it often creates unexpected beneficial effects in the physicochemical properties of the nanosystem . Various nanostructured materials, including carbons, magnetics, , silicon clusters, and host–guest inclusion compounds, have been explored by irradiation with energetic particles, and have produced breakthroughs in their inherent properties. Recently, energetic particle irradiated clathrate hydrates have been intensively examined to shed light on functionalized icy materials.…”
Section: Introductionmentioning
confidence: 99%